1997
DOI: 10.3109/00016359709115414
|View full text |Cite
|
Sign up to set email alerts
|

A Scanning Electron Microscopy Study of Disturbances in the Developing Rat Molar Induced by Cyclophosphamide

Abstract: Scanning electron microscopy was used to study the effect of cyclophosphamide (Cy) on molar development in 18 Sprague-Dawley rats from 15 to 48 days of age after birth. Doses of 30 mg/kg body weight of Cy dissolved in 1 ml 0.9% NaCl were given to the rats at 10 and 13 days of age. Eighteen control rats had injections of 1 ml 0.9% NaCl at the same ages. The most obvious changes in the experimental teeth were found in the developing roots of the first and second molars and in both the crown and roots of the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…Chemotherapeutic agents cyclophosphamide and doxorubicin are known to interfere with dental development after cessation of treatment in rats [20,21]. Medication with the antracyclines and platina agents disturb dentin matrix secretion and collagen fibril formation and cause short, thin, tapered roots [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic agents cyclophosphamide and doxorubicin are known to interfere with dental development after cessation of treatment in rats [20,21]. Medication with the antracyclines and platina agents disturb dentin matrix secretion and collagen fibril formation and cause short, thin, tapered roots [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models and in vitro studies have demonstrated dose-dependent dental disturbances caused by cyclophosphamide, primarily on the continually growing rat incisor. [32][33][34][35][36][37][38][39][40][41][42] Cyclophosphamide administered in growing rats resulted in shortened roots and reduced crown size of molars. It was shown that the roots of the rat molars rarely reached two-thirds of the normal root length, accompanied by closure of root apices.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the roots of the rat molars rarely reached two-thirds of the normal root length, accompanied by closure of root apices. 35 It was suggested that cyclophosphamide induced root shortening by disturbing the cells in Hertwig's root sheath and that early apical closure occurred due to formation of osteodentin. 36 Clinical demonstrations of the dental effects of cyclophosphamide (or chemotherapy alone) are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using objective measurements to quantify the developmental aberrations are rare. Area measurements of dental crowns and/or roots, ratios of root and crown areas,14, 23, 28 or root‐crown (R/C) ratios based on tooth length measurements25 have been used. Calcification of permanent teeth begins at the time or soon after the birth, taking approximately 15 years when the third molars are excluded 29, 30.…”
mentioning
confidence: 99%